ANALISIS KINERJA KEUANGAN PADA PT.GARUDA INDONESIA (PERSERO) TBK ANTARA SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) SELAMA PERIODE 2008-2013 - A CAHYA LESTARI, M Cahya (Jurnal Akuntansi AKUNESA, 2014)
The purpose of the study is to analyze the financial performance of PT. Garuda Indonesia (Persero) Tbk before and after Initial Public Offering (IPO) during the period of 2008 – 2013. The analysis of the financial performance was conducted using the financial ratio. The ratio was calculated from the financial reports that have been published by the company in three years before and after the IPO. The result of the study can be concluded that three years after IPO, the financial performance showed a reduction compared to the financial performance three years before IPO even though still in the category A. Collection periods, inventory turn over, total asset turn over still showed good values before and after IPO. Cash ratio, current ratio and TMS/TA values were increased while ROE and ROI showed values reduction after IPO.Keyword: initial public offering, financial performance, financial ratio